2018
DOI: 10.31462/jcemi.2018.01043054
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of energy-cost efficient design alternatives for residential buildings

Abstract: A considerable amount of energy is consumed in buildings because of the economic developments and the increased population. By taking in consideration that 40% of total energy use is consumed in the building, the proper design of building's envelope is crucial for reducing the adverse effects of high energy consumption in the economy and environment of a country. This study aims to investigate the proper design alternatives on the reduction of energy consumption and life-cycle cost (LCC) of residential buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Several studies are reported in the literature for building envelope materials and parameters to reduce operation energy. Among these studies, changing the different parameters of the building envelope in a reference building and finding the scenario with the most energy efficient combinations are a topic of great importance [7][8][9][10]. For example, Mirrahimi et al [11] showed that building envelope parameters (window/wall ratio, wall type, building orientation, glazing, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Several studies are reported in the literature for building envelope materials and parameters to reduce operation energy. Among these studies, changing the different parameters of the building envelope in a reference building and finding the scenario with the most energy efficient combinations are a topic of great importance [7][8][9][10]. For example, Mirrahimi et al [11] showed that building envelope parameters (window/wall ratio, wall type, building orientation, glazing, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…caused by this inevitable increase show themselves more markedly. To minimize these kinds of problems a series of mandatory and encouraging policies have been implementing in many sectors especially in developed and developing countries [1]. Among these sectors, the construction sector consumes a significant amount of energy, such as 40 % of the total energy consumption [2].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the heat gains are 25 -35% in roofs, 25 -35% in windows, 15 -25% in walls, 10 -20% ground floors, and 5 -25% air infiltration. More heat losses and gains are translated into more energy consumption to maintain the thermal comfort [7].…”
Section: Introductionmentioning
confidence: 99%
“…The most energy efficient combination is low-e glass + 100 mm (Expandable Polystyrene) EPS + Window Wall Ratio (WWR) 50% for cold climate regions and reflective glass + 100 mm EPS + WWR 50% for hot climate region. Also, the most cost-efficient combination is clear glass + 100 mm EPS + WWR 50% for both regions [7].…”
Section: Introductionmentioning
confidence: 99%